2020
DOI: 10.1149/2162-8777/ab85c0
|View full text |Cite
|
Sign up to set email alerts
|

Light Extraction Efficiency Optimization of AlGaN-Based Deep-Ultraviolet Light-Emitting Diodes

Abstract: Using finite-difference time-domain method, the light extraction efficiency (LEE) of AlGaN-based deep-ultraviolet light-emitting diodes (DUV LEDs) is investigated. Simulation results show that compared to flat sapphire substrate, the nano-patterned sapphire substrate (NPSS) expands the extraction angles of top surface and sidewalls. As a result, the LEE of transverse-magnetic (TM) polarized light is improved significantly. Roughening on the backside of n-AlGaN surface significantly enhances the LEE of top surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The NPSS improves TM-polarized light extraction reflected by the Al/Si inclined sidewall. 33 Figure 4c shows the EQE trend of the measured devices under CW biasing conditions. All of the UV-LED devices show efficiency droop at high injection currents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPSS improves TM-polarized light extraction reflected by the Al/Si inclined sidewall. 33 Figure 4c shows the EQE trend of the measured devices under CW biasing conditions. All of the UV-LED devices show efficiency droop at high injection currents.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was demonstrated that the NPSS could significantly enhance the UV-LED light extraction from sidewalls by scattering at the interface of sapphire and AlN. The NPSS improves TM-polarized light extraction reflected by the Al/Si inclined sidewall …”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we have investigated the LEE of DUV LEDs using FDTD method. 132 The results showed that NPSS could enhance the LEE of TM-polarized lights significantly, as compared to FSS. Furthermore, the LEE of flip-chip…”
Section: Influence Of Structural Parameters Of Pss On Led Propertiesmentioning
confidence: 93%
“…In our previous study, we have investigated the LEE of DUV LEDs using FDTD method. 132 The results showed that NPSS could enhance the LEE of TM-polarized lights significantly, as compared to FSS. Furthermore, the LEE of flip-chip LED on NPSS was estimated to be about 15%, which was ∼50% higher than that of flip-chip DUV LED with rough n-AlGaN surface (Fig.…”
Section: Influence Of Structural Parameters Of Pss On Led Propertiesmentioning
confidence: 93%
“…For example, growing AlN film on the SiC substrate can effectively reduce the dislocation of AlN due to the similar lattice matching between the SiC substrate and AlN epitaxial layer, but the expensive SiC substrate increases the cost of producing DUV-LEDs [12,13]. In addition, the high-quality AlN epitaxial layers can be obtained on the nanopatterned sapphire substrate (NPSS), which effectively improves the internal quantum efficiency of DUV-LEDs [14][15][16]. However, due to the large migration barrier of Al atoms on the surface of NPSS, the growth mode of Al atoms follows the 3D Volmer-Weber growth mode.…”
Section: Introductionmentioning
confidence: 99%